Faktor-Faktor Yang Berhubungan Dengan Tingkat Kecemasan Orang Tua Selama Menunggu Anaknya Menjalani Tindakan Operasi Di RS Wilayah Jakarta - Sihombing, Enna Rossalina; Muhamad Hilman; Paramitha Wirdani Ningsih Marlina (Journal of Pubnursing Sciences, 2023)
Introduction: Surgery is a stressor that requires physical and psychosocial adaptation both for patients and families and this stressor will create anxiety. Objective: This study aims to find out the factors related to the level of parents' anxiety while waiting for their children to undergo surgery at the hospital in Jakarta area. Method: This research uses a descriptive correlation method with a cross-sectional approach. Data was collected with a questionnaire of 80 respondents, namely parents who were waiting for their children who were undergoing operations at the hospital in Jakarta area. Sampling technique is total sampling. This study was conducted in May-August 2022 in the family waiting room who were undergoing operational actions at the hospital in Jakarta area. This study uses a questionnaire as a measurement tool, a statistical test using the Chi-Square Test. Results: There is no relationship between age (p value: 0.754), sex (p value: 0.774), education (p value: 0.599) and work (p value: 0.673) with an anxiety level of parents. While the surgery time (p value: 0.010), experience (p value: 0.028), type of operation (p value: 0.021) and type of anesthesia anathesi (p value: 0.036) has something to do with the level of anxiety of parents while waiting for their children to carry out the action Operations at hospitals in Jakarta area. Conclusion: There is no relationship between age, gender, education and work with the level of anxiety of parents while waiting for their children to carry out operations at the hospital in Jakarta area. Whereas the time of surgery, experience, type of operation and type of anesthesia has to do with the level of anxiety of parents of parents while waiting for their children to carry out surgery at the hospital in Jakarta area